A Battery-less Grid Connected Photovoltaic Power generation using Five-Level Common-Emitter Current-Source Inverter - Suroso Suroso; Winasis Winasis; Toshihiko Noguchi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
Renewable power generation using photovoltaic is very interesting to be developed to deal with the problems of conventional energy sources and environmental issues. The photovoltaic power generation can operate both in stand-alone and grid-connected operations. This paper presents an application of the five-level common-emitter current-source inverter (CE-CSI) for grid connected photovoltaic system without batteries as energy storage system. In the proposed system, the five-level CE-CSI works generating a sinusoidal output current from photovoltaic system to be injected into the power grid. The transformer is used in the system to step-down the grid voltage to meet the voltage level of the photovoltaic system, and also works as a galvanic insulation between the power grid and the inverter system. Two conditions of the power grid voltage, i.e. a pure sinusoidal and a distorted power grid, are tested through computer simulation using PSIM software. Furthermore, experimental test result of the five-level inverter is also presented. The test results show that the five-level CE-CSI works well injecting a sinusoidal current into the power grid with low harmonic contents, and with unity power factor operation. The results also show that the distorted grid voltage affects the harmonic contents of the current injected by the inverter.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6464